Congenital pulmonary lymphangiectasia and early mortality after stage 1 reconstruction procedures*. (13th March 2017) - Herrmann, Jeremy L.; Irons, Mallory L.; Mascio, Christopher E.; Rychik, Jack; Spray, Thomas L.; Gaynor, J. William; Pogoriler, Jennifer E.
Abstract: Objectives: Pulmonary lymphangiectasia associated with hypoplastic left heart syndrome with an intact or restrictive atrial septum may result from increased left atrial pressure, and is associated with worse outcomes following staged reconstruction due to lung dysfunction and significant hypoxaemia. Our objective was to characterise the incidence of pulmonary lymphangiectasia in cases of early mortality following stage 1 reconstructions. Methods: An institutional cardiac surgical database was retrospectively searched for patients who died within 30 days following a stage 1 reconstruction between 1 January, 1984 and 31 December, 2013. During that period, 1669 stage 1 procedures were performed. Autopsy lung specimens were reviewed by a paediatric pathologist. Patients who died of suspected technical issues were excluded. Results: A total of 54 patients were included, and of these seven cases (8.5%) of pulmonary lymphangiectasia were identified. The mean estimated gestational age was 38.2±2.4 weeks, and the mean birth weight was 3.0±0.6 kg. The median interval between surgery and death was 1 day (with a range from 0 to 18 days). The atrial septum was intact in one patient (14.3%), restrictive in three patients (42.9%), and unrestrictive in three patients (42.9%). Conclusions: Pulmonary lymphangiectasia may develop in hypoplastic left heart syndrome with or without a restrictive atrial septum. As standard prenatal diagnostic evaluations and treatment methods for pulmonary lymphangiectasia are limited, this may be an important contributor to early and late mortality following stage 1 reconstruction for hypoplastic left heart syndrome.